Pengaruh Brand Image Dan Customer Experience Terhadap Repurchase Intention Dengan Brand Trust Sebagai Variabel Intervening Pada J.Co Donuts & Coffee Paragon Mall Dan Java Supermall Semarang - Rahmanda, Fakhri; Farida, Naili (Universitas Diponegoro, 2021)
Abstract: The phenomenon that occurs in the field says that there is a decrease in income and also the number of consumers who are not satisfied with the services provided by J.Co Donuts and Coffee, especially at the Semarang branch, are the basis of the problem why this research was carried out. Then an empirical research model is built on brand image and customer experience on repurchase intention as well as problems regarding repurchase intention through the concept of brand trust. This study aims to determine how the influence of brand image and customer experience on repurchase intention through brand trust at J.Co Donuts and Coffee Semarang using explanatory research and accidental sampling methods combined with purposive sampling. The research sample consisted of 104 J.Co Donuts consumers. and Coffee Semarang Branch. Then the data obtained were analyzed quantitatively using the SPSS (Statistical Package for Social Science) program to determine the effect of exogenous variables on endogenous variables in this study. This study resulted in the findings that brand image is proven to have an influence on brand trust, customer experience is proven to have an effect on brand trust, brand image and customer experience is proven to have an effect on brand trust, brand trust is proven to have an influence on repurchase intention.Â Keywords: Repurchase Intention; Brand Trust; Brand ImageÂ Abstrak: Fenomena yang terjadi di lapangan mengatakan bahwa terjadi penurunan pendapatan dan juga banyaknya konsumen yang tidak puas terhadap pelayanan yang dilakukan oleh J.Co Donuts and Coffee khususnya pada Cabang Semarang menjadi dasar permasalahan mengapa penelitian ini dilaksanakan. Kemudian dibangun model penelitian empirik brand image dan customer experience terhadap repurchase intention serta permasalahan tentang repurchase intention melalui konsep brand trust. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh brand image dan customer experience terhadap repurchase intention melalui brand trust di J.Co Donuts and Coffee semarang dengan menggunakan dasar penelitian explanatory research dan metode accidental samplingyang dipadu dengan purposive sampling.Sampel penelitian sebanyak 104 konsumen J.Co Donuts and Coffee Cabang Semarang. Kemudian data yang diperoleh dianalisis secara kuantitatif dengan menggunakan program SPSS (Statistical Package for Social Science) untuk mengetahui pengaruh dari variabel eksogen terhadap variabel endogen dalam penelitian ini. Penelitian ini menghasilkan temuan bahwa brand image terbukti mempunyai pengaruh terhadap brand trust, customer experience terbukti berpengaruh terhadap brand trust, brand image dan customer experience terbukti berpengaruh terhadap brand trust, brand trust terbukti mempunyai pengaruh terhadap repurchase intention.Â Kata Kunci: Repurchase Intention; Brand Trust; Brand Image